Isolation and molecular characterization of the indigenous Staphylococcus aureus strain K1 with the ability to reduce hexavalent chromium for its application in bioremediation of metal-contaminated sites - Muhammad Tariq; Muhammad Waseem; Muhammad Hidayat Rasool; Muhammad Asif Zahoor; Irshad Hussain (PeerJ, 2019)
Background Urbanization and industrialization are the main anthropogenic activities that are adding toxic heavy metals to the environment. Among these, chromium (in hexavalent: Cr+6 and/or trivalent Cr+3) is being released abundantly in wastewater due to its uses in different industrial processes. It becomes highly mutagenic and carcinogenic once it enters the cell through sulfate uptake pathways after interacting with cellular proteins and nucleic acids. However, Cr+6 can be bio-converted into more stable, less toxic and insoluble trivalent chromium using microbes. Hence in this study, we have made efforts to utilize chromium tolerant bacteria for bio-reduction of Cr+6 to Cr+3. Methods Bacterial isolate, K1, from metal contaminated industrial effluent from Kala Shah Kaku-Lahore Pakistan, which tolerated up to 22 mM of Cr6+ was evaluated for chromate reduction. It was further characterized biochemically and molecularly by VITEK®2 system and 16S rRNA gene sequencing respectively. Other factors affecting the reduction of chromium such as initial chromate ion concentration, pH, temperature, contact-time were also investigated. The role of cellular surface in sorption of Cr6+ ion was analyzed by FTIR spectroscopy. Results Both biochemical and phylogenetic analyses confirmed that strain K1 was Staphylococcusaureus that could reduce 99% of Cr6+ in 24 hours at 35 °C (pH = 8.0; initial Cr6+ concentration = 100 mg/L). FTIR results assumed that carboxyl, amino and phosphate groups of cell wall were involved in complexation with chromium. Our results suggested that Staphylococcusaureus K1 could be a promising gram-positive bacterium that might be utilized to remove chromium from metal polluted environments.